2020
DOI: 10.1093/cid/ciaa1185
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster and Postherpetic Neuralgia: Changing Incidence Rates From 1994 to 2018 in the United States

Abstract: Introduction The incidence of herpes zoster (HZ) has been increasing in recent decades. Although two vaccines for HZ are available, there have been few studies on the incidence rates of HZ and post-herpetic neuralgia (PHN) since their introduction. This study examined the incidence rates of HZ and PHN from 1994-2018 in the United States to determine if they have continued to increase since introduction of the herpes zoster vaccines. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 32 publications
5
46
0
Order By: Relevance
“…PHN is a common, yet troublesome to treat, neuropathic pain ( 1 , 2 ). In recent years, the incidence of PHN has increased yearly with the incidence of herpes zoster ( 3 , 4 ). The incidence of PHN in the United States has been reported to be as high as 57.5 cases/(100,000 persons/year) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHN is a common, yet troublesome to treat, neuropathic pain ( 1 , 2 ). In recent years, the incidence of PHN has increased yearly with the incidence of herpes zoster ( 3 , 4 ). The incidence of PHN in the United States has been reported to be as high as 57.5 cases/(100,000 persons/year) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the incidence of PHN has increased yearly with the incidence of herpes zoster ( 3 , 4 ). The incidence of PHN in the United States has been reported to be as high as 57.5 cases/(100,000 persons/year) ( 4 ). In China, the incidence of PHN is even higher, with statistics pointing to an incidence of 2.3% ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of herpes zoster and progression to PHN adds to this burden and causes a marked decline in the overall functional status of affected patients [6]. In contrast to expectations created with the advent of herpes zoster vaccines, a recent large epidemiological study from 1994 to 2018 showed that the overall incidence rates of PHN continued to increase annually in the USA [7].…”
mentioning
confidence: 99%
“…Later in life, or under a state of compromised immunity, the virus can re-emerge and trigger a unilateral, painful, vesicular rash along the distribution of a dermatome. In European countries and the US, the annual incidence of herpes zoster is estimated at approximately 1-6.2 per 1,000 persons (4)(5)(6)(7).…”
mentioning
confidence: 99%